2017
DOI: 10.1007/s11605-017-3571-2
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Site Infection Is Associated with Tumor Recurrence in Patients with Extrahepatic Biliary Malignancies

Abstract: Background Surgical site infections (SSI) are one of the most common complications after hepato-pancreato-biliary surgery. Complications may lead to an associated immune-modulatory effect that inhibits the body’s response to cancer surveillance. We sought to define the impact of SSI on long-term prognosis of patients undergoing surgical resection of extra-hepatic bilary malignancies (EHBM). Methods Patients undergoing surgery for EHBM between 2000 and 2014 were identified using a large, multi-center, nationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Independent prognostic factors include hepatic invasion, lymph node metastasis, and surgical margin status 9,11‐13 . Specifically, lymph node status is a strong predictor of OS 9,11 .…”
Section: Discussionmentioning
confidence: 99%
“…Independent prognostic factors include hepatic invasion, lymph node metastasis, and surgical margin status 9,11‐13 . Specifically, lymph node status is a strong predictor of OS 9,11 .…”
Section: Discussionmentioning
confidence: 99%
“…Infective postoperative complications (Inf‐POC) included respiratory tract infection, catheter‐related bloodstream infection, urinary tract infection, and surgical site infection (intraabdominal collection, wound infection or biliary fistula). To be diagnosed with Inf‐POC, patients had to present clinical systemic (such as fever) or local (such as local pain or swelling) symptoms; and/or compatible diagnostic imaging; and/or isolation of microorganisms in body fluids or tissues 15 . Noninfective postoperative complications (Non‐inf POC) included paralytic ileus, liver failure, renal failure, postoperative hemorrhage, pulmonary (noninfective), and cardiac complications.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, a direct influence on the overall outcome for the patient has been demonstrated. Buettner et al showed a deterioration of recurrence-free survival and overall survival after curative-intended resections of extrahepatic bile duct malignancies [ 9 ]. Furthermore, similar results have been shown in cases of hepatic resection of colorectal liver metastases [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…SSIs account for a large proportion of nosocomial infections [ 3 , 4 ] and often lead to revision operations [ 5 ], prolonged hospital stays, increased costs [ 6 , 7 ], and a reduction in patient quality of life [ 8 ]. In addition, they have been shown to worsen the overall outcome in oncological patients [ 9 , 10 ].…”
Section: Rationalementioning
confidence: 99%